RISK GROUPS FOR PREGNANCY HYPERTENSIVE DISORDERS DEVELOPMENT - N. A. Shakhbazova (Российский кардиологический журнал)
Aim.  Development of clinical, anamnestic, immunological and instrumental prognostic markers of high and low risk of gestational hypertensive disorders.Material and methods. A range of risk factors was assessed in 220 pregnant women with hypertensive states (main group) and 50 healthy pregant women (control group). In the pregnant, clinical and anamnestic risk factors of preeclampsia were assessed (age, parity, anamnesis of hypertensive disorders, extragenital diseases, etc.), autoantibodies to 12 antigenes (by ELI-P test), placental growth factor (PGF) and resistance index (RI) in uterus arteries, by Doppler.Results. During the study, it was found that clinical and anamnestic factors of high risk of pre-eclampsia are: first pregnancy, chronic hypertension, extragenital pathology in woman, anamnesis of pre- and eclampsia, combination of three and more factors. Preclinical immunological predictors of high risk of pre-eclampsia in the 1st trimester are high titre of autoantibodies to S-100, B-2QP, ANCA (range -65 to +94 units), combined raise of three kinds of antibodies, immunity suppression, PGF level in the blood 50-100 pg/mL — for pre-eclampsia, up to 50 pg/mL — for fetal development delay. Doppler markers of high risk of pre-eclampsia: increase of RI up to 0,60 and dicrotic notch in both uterine arteries; RI increase 0,61-0,70 with one dicrotic notch only in one uterine artery; increase of RI more than 0,70 and no dicrotic notch. Conclusion. The most useful and predictive for pre-eclampsia are clinical and anamnestic, as immunological predictors that are revealed within 15 weeks of pregnancy. Instrumental prognostic markers that are explored after 20 weeks are useful for prognosis prediction on possible pre-eclampsia development and for control of treatment efficacy.